Parents’ Perceptions of Heritage Languages in the Mid-West: Facing the Challenge of Losing One’s Native Language in Kansas - Abdelliah Salim Sehlaoui; Rihab Mousa (The Advocate, 2016)
While heritage language research tends to focus on populations in the Eastern and Western coasts of the country, little if anything is known about heritage language loss, use, perceptions, or what parents do to overcome the challenges their children face on a daily basis in Midwest states such as Kansas, especially in remote rural areas. The present study aims at making the voices of some of these parents heard by describing the common themes that emerged from the qualitative data analysis collected from their perceptions towards heritage languages in the state of Kansas. The paper provides a brief description of the sociolinguistic context, includes a brief literature review, describes the methodology used in data collection and analysis, summarizes data results, discusses the common patterns, and offers some conclusions and recommendations. The main research questions were: How do parents perceive heritage language use in their families and communities? What do they do to preserve their heritage language in their families and communities? To what extent are these parents able to analyze the causes of heritage language loss and societal attitudes from a critical and macro-level of analysis?